Application of pulse power supply for diamond coatings deposition in glow discharge plasma - Koshevoy, K.I.; Volkov, Yu.Ya.; Strel’nitskij, V.E.; Reshetnyak, E.N. (Вопросы атомной науки и техники, 2019)
Comparative studies of diamond coatings deposition have been carried out in the glow discharge plasma stabilized by a magnetic field in methane-hydrogen medium with using the DC or pulse power supply. It was shown that using of a pulsed power supply leads to an increase of the input power range at which the discharge is stable in comparison with DC one. In addition a significant increase of the samples temperature and the diamond coating growth rate were achieved at the same average power introduced into the discharge. The resulting diamond coating was of high quality and purity.